(untitled) (Fiep Bulletin - online, 2012)
The aim of this study is to investigate studies involving physical fitness of indigenous populations. This bibliographical study is based on the analysis of articles published in the last 10 years available on the internet from digital journals of the Virtual Health Library (BIREME) and the Scientific Electronic Library Online (SciELO). The terms used in these studies involving physical fitness of indigenous populations are varied and most frequently based on anthropometry followed by physical growth. The measurements used in the study of physical fitness in indigenous peoples are weight, structure, circumference and skin folds, being that most studies are based on weight and height measurements. Most studies adopted the procedures recommended by the World Health Organization. The most widely adopted reference values are recommended by the World Health Organization (WHO), based on the reference population of the National Center for Health Statistics (NCHS). Studies did not include cultural adaptations in terms of protocols or references in studies involving indigenous populations, as recommended by the WHO.